A study on the factors of employee empowerment on work performance in manufacturing industry - Siti Solehan, Tajuddin (2013)
This research aims to investigate the relationship between factors of empowerment and employee performance in the manufacturing industry. It also aims to examine the influence of empowerment on employee performance and to identify which of the four (4) factors of empowerment has the greatest influence on employee performance. The four factors of empowerment, namely participation of empowerment, delegation of authority, training and rewards, are the identified independent variables, with employee performance as the dependent variable. Each of the dimensions of empowerment was tested to determine its relationship with employee performance. The questionnaires were sent to 108 respondents to fill it. A total of 104 respondents from 108 respondents participated in the survey. The participating respondents represented a return rate of 96% from 100%. Five (5) hypotheses were developed and tested using Pearson Correlation and Regression Analysis. The findings indicate that employees in Kilang Sawit RISDA find that empowerment moderately influences employee performance. There is significant correlation between the factors of empowerment and employee performance. They feel that when they are empowered with participation in decision making, delegation of authority, training and rewards, their performance will improve significantly. The implications of these findings are discussed and suggestions for future research are also identified and proposed.